Can Minimally Invasive Multivessel Coronary Revascularization Be a Routine Approach? - Kyaruzi, Mugisha; Gülmez, Harun; Demirsoy, Ergun (The Thoracic and Cardiovascular Surgeon, 2022)
Background Advancement in the field of cardiovascular surgery has emerged with various minimally invasive approaches for the treatment of multivessel coronary disease to improve outcomes and minimize the burden associated with conventional cardiac surgery. This study describes our routine technical approach and clinical experience of minimally invasive coronary artery bypass via left anterior minithoracotomy for the treatment of patients with multivessel coronary lesions.Methods Our experience includes 100 consecutive patients who were operated between July 2020 and April 2021. The left internal thoracic artery was harvested in all patients. Radial arterial grafts and saphenous vein grafts were harvested endoscopically. Patients were operated either under cardiopulmonary bypass (CPB) with blood cardioplegia through left anterior minithoracotomy of 5 to 7 cm or off-pump via left anterolateral minithoracotomy.Results We had single mortality (1%), no early postoperative myocardial infarction was observed. None of our patients was converted to sternotomy (0%). The mean number of bypass was 3.1 ± 0.8, the mean cross-clamping time was 78.1 ± 20.6 minutes, the mean CPB time was 153.2 ± 37.5 minutes, the average intubation time was 6.33 ± 11.29 hours, the mean intensive care unit stay was 1.62 ± 1.78 days, the mean hospital stay was 4.98 ± 3.01 days, the average total operation time was 4.20 ± 0.92 hours, and the average pleural drain was 393.8 ± 169.7 mL.Conclusion Minimally invasive coronary artery bypass grafting via left anterior minithoracotomy can be routinely performed with safety and it is feasible, reproducible with a short learning curve. Further multicenter studies are needed for the standardization of our technique.
Keywords: minimal invasive surgery (minithoracotomy); cardiopulmonary bypass; coronary artery bypass grafting